Toxicity and motor changes in africanized honey bees (Apis mellifera l.) exposed to fipronil and imidacloprid - Bovi, Thaís S. [UNESP]; Zaluski, Rodrigo [UNESP]; Orsi, Ricardo de Oliveira [UNESP] (FapUNIFESP (SciELO), 2018)
This study evaluated the in vitro toxicity and motor activity changes in African-derived adult honey bees (Apis mellifera L.) exposed to lethal or sublethal doses of the insecticides fipronil and imidacloprid. Mortality of bees was assessed to determine the ingestion and contact lethal dose for 24 h using probit analysis. Motor activities in bees exposed to lethal (LD50) and sublethal doses (1/500thof the lethal dose) of both insecticides were evaluated in a behavioral observation box at 1 and 4 h. Ingestion and contact lethal doses of fipronil were 0.2316 ± 0.0626 and 0.0080 ± 0.0021 mg/bee, respectively. Ingestion and contact lethal doses of imidacloprid were 0.1079 ± 0.0375 and 0.0308 ± 0.0218 mg/bee, respectively. Motor function of bees exposed to lethal doses of fipronil and imidacloprid was impaired; exposure to sublethal doses of fipronil but not imidacloprid impaired motor function. The insecticides evaluated in this study were highly toxic to African-derived A. mellifera and caused impaired motor function in these pollinators.
Keywords: Contamination; Environment; Neonicotinoids; Pesticides; Phenylpyrazoles; Pollinators